Merske značilnosti skrajšanega protokola meritev dinamičnega ravnotežja z napravo Y-test - Spudić, Darjan (Šport (Ljubljana), 2019)
The aim of the study was to access intra- and inter-visit reliability of the custom-made Y-balance test device parameters. It was developed to standardise the modified "Star Excursion Balance Test", improve its practicality, and make it commercially available. An individual%s reaching distance in a given direction was found to be correlated with his or her reaching distance in the other 7 directions. This has led to the recommendation that only 3 reach directions (anterior, posteromedial, and posterolateral) should be performed. In comparison to other studies, shorter, though timesaving testing protocol was developed. Reliability was checked using intraclass correlation coefficient, standard error of measurement and smallest real difference parameters. 30 PE students volunteered to participate in the study. The study was designed in a test-retest manner. On every visit, participants executed 2 measuring sets. Paired samples t-test showed some significant differences among inter- and intra-visit results, that is in one third and one half of all parameters analysed, respectively. ICC showed fair to excellent reliability (ICC 0,524-1,000), excluding results in posteromedial direction (ICC < 0,5). Standard error of measurement values ranged 0,014-5,808 cm and values of smallest real difference ranged 0,5-16 %. We noticed no differences between using the maximal distance achieved or average value of two consecutive measures parameters. We found our testing protocol and parameters useful in sports performance, specifically in dynamic balance and contralateral lower limb differences testing. Due to a higher standard error of measurement and a relatively high smallest real difference in posteromedial distance results, we agree that clinical practice usefulness should be questioned. Consistency of the testing protocol and reliability parameters should be considered when testing and, later, interpreting testing results.
Keywords: balance; ponovljivost; protokol; ravnotežje; reliability; repeatibility; sport; šport; testing; Y-test; zanesljivost